Nuclear energy: Where do we go from here? - Muslim N. (American Institute of Physics Inc., 2023)
As Malaysia progresses towards 2020, the depleting resource of oil and gas has forced a re-look at alternatives to replace fossil fuels as energy sources. Among the viable options is nuclear energy, enabling us to meet energy needs and sustain national development in the twenty-first century. Three essential steps Malaysia must take to introduce nuclear power into its energy mix are: energy planning, infrastructure development, and deployment. Malaysia has to face a series of challenges, including public acceptance, waste management, minimizing proliferation risk, and ensuring the security of nuclear plants and materials. Timely development of qualified and competent manpower is a key limiting factor in the development and transfer of nuclear technologies - and education and training take time, effort and money. There is a need for political will. Within the Asian region, China, Korea and Japan are in the forefront in utilizing nuclear power to meet electricity demands. Countries such as UAE, Bangladesh, Vietnam and Turkey are moving ahead with the nuclear option for electricity generation and they have begun planning and construction of nuclear power plants. Against this backdrop, what are Malaysia's moves? This paper discusses various options and challenges, obstacles and repercussions in meeting future energy demands. 2015 AIP Publishing LLC.